Determining collaboration between University of Florida Institute of Food and Agricultural Sciences Extension agents and secondary school-based agricultural educators - Case Emerson; Brian E. Myers; J. C. Bunch; Jason Dossett (Advancements in Agricultural Development, 2024)
Successful and beneficial collaboration relies on the dedication individuals to cooperate, the established culture of collaboration and cooperation and a desire and willingness to collaborate. Agricultural educators and Extension agents often find themselves in competition for members rather than cooperation to develop members. Working in conjunction with one another in a concerted effort allows the two groups to develop youth into more efficient and effective leaders and citizens. This study utilized the Theory of Planned Behavior (Ajzen, 1985). As applied to this study, this theory would hold that the variables of interest, personal and professional demographics within the two groups, to influence collaboration levels between agricultural educators and extension agents because these factors can shape and include attitudes, subjective norms, and perceived behavioral controls. This study found perceptions between school-based agricultural educators and Extension agents do hold positive views of cooperation. However, this cooperation does not happen very often outside of well-established instances. Upon examination of this study, we recommend further research be done to maintain an accurate reading of cooperation between these two entities and delve further into what motivates them.